Investigation on the clusterability of mixed variables based on simulated dataset from simmulticorrdata package / Norin Rahayu Shamsuddin and Nor Idayu Mahat - Shamsuddin, Norin Rahayu; Mahat, Nor Idayu (Universiti Teknologi MARA, Perak, 2019)
Mixed-type variables gain significant attention in clustering as widely observed in real datasets. The construction of clustering or clusterability of mixed dataset seems hard to form owing to a different scale in data. The current paper assessed the impact of clusters structures that developed from simulation data of mixed data types derived from different distributions through the R package SimMultiCorrData that mimics the real-world scenario. This particular package was therefore adopted to acquire mixed variables simulation data and investigated the clusterability of mixed variables in a dataset.